Phân tích đa thức thành nhân tử:
a, x2 - 4y2
b,x2 + x - 12
c, x2 + 2xy + y2 - 11
d, x4 + 1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=\left(\frac{1}{x+1}+\frac{1}{x-1}\right):\frac{2x}{x-1}\)
a) Điều kiện xác định:
\(\hept{\begin{cases}x+1\ne0\\x-1\ne0\\2x\ne0\end{cases}}\Rightarrow\hept{\begin{cases}x\ne0-1\\x\ne0+1\\x\ne0\end{cases}}\Rightarrow\hept{\begin{cases}x\ne-1\\x\ne1\\x\ne0\end{cases}}\)
Vậy để P có nghĩa thì \(x\ne-1;x\ne1\) và \(x\ne0.\)
b) Rút gọn:
\(P=\left(\frac{1}{x+1}+\frac{1}{x-1}\right):\frac{2x}{x-1}\)
\(P=\left(\frac{1.\left(x-1\right)}{\left(x-1\right).\left(x+1\right)}+\frac{1.\left(x+1\right)}{\left(x-1\right).\left(x+1\right)}\right):\frac{2x}{x-1}\)
\(P=\left(\frac{x-1}{\left(x-1\right).\left(x+1\right)}+\frac{x+1}{\left(x-1\right).\left(x+1\right)}\right):\frac{2x}{x-1}\)
\(P=\left(\frac{x-1+x+1}{\left(x-1\right).\left(x+1\right)}\right):\frac{2x}{x-1}\)
\(P=\frac{2x}{\left(x-1\right).\left(x+1\right)}:\frac{2x}{x-1}\)
\(P=\frac{2x}{\left(x-1\right).\left(x+1\right)}.\frac{x-1}{2x}\)
\(P=\frac{2x.\left(x-1\right)}{2x.\left(x-1\right).\left(x+1\right)}\)
\(P=\frac{1}{x+1}.\)
a. \(\frac{2x+3}{15}=\frac{7}{5}\)
\(\Leftrightarrow5\left(2x+3\right)=15.7\)
\(\Leftrightarrow10x+15=105\)
\(\Leftrightarrow10x=90\)
\(\Leftrightarrow x=9\)
b. \(\frac{x-2}{9}=\frac{8}{3}\)
\(\Leftrightarrow3\left(x-2\right)=9.8\)
\(\Leftrightarrow3x-6=72\)
\(\Leftrightarrow3x=78\)
\(\Leftrightarrow x=26\)
c. \(\frac{-8}{x}=\frac{-x}{18}\)
\(\Leftrightarrow-x^2=-144\)
\(\Leftrightarrow x^2=12^2\)
\(\Leftrightarrow\orbr{\begin{cases}x=12\\x=-12\end{cases}}\)
Mấy câu kia tương tự
d, \(\frac{2x+3}{6}=\frac{x-2}{5}\Leftrightarrow10x+15=6x-12\Leftrightarrow4x=-27\Leftrightarrow x=-\frac{27}{4}\)
e, \(\frac{x+1}{22}=\frac{6}{x}\Leftrightarrow x^2+x=132\Leftrightarrow x^2+x-132=0\Leftrightarrow\left(x-11\right)\left(x+12\right)=0\Leftrightarrow\orbr{\begin{cases}x=11\\x=-12\end{cases}}\)
f, \(\frac{2x-1}{2}=\frac{5}{x}\Leftrightarrow2x^2-x=10\Leftrightarrow2x^2-x-10=0\Leftrightarrow\left(x+2\right)\left(2x-5\right)=0\Leftrightarrow\orbr{\begin{cases}x=-2\\x=\frac{5}{2}\end{cases}}\)
g, \(\left(2x-1\right)\left(2x+1\right)=63\Leftrightarrow4x^2+2x-2x-1=63\Leftrightarrow4x^2-64=0\)
\(\Leftrightarrow x^2=16\Leftrightarrow x=\pm4\)
h, \(\frac{10x+5}{6}=\frac{5}{x+1}\Leftrightarrow\left(10x+5\right)\left(x+1\right)=30\Leftrightarrow10x^2+10x+5x+5=30\)
\(\Leftrightarrow10x^2+15x-25=0\Leftrightarrow5\left(2x+5\right)\left(x-1\right)=0\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{2}\\x=1\end{cases}}\)
1. encourage
2. necessity
3. fashionable
4. Modernization
1.I study at International Secondary School.
2.I am in grade six and I am in class 6A.
3.There are three buildings and a swimming pool in my school.
4.My class is on the first floor of the building A.
5.My favorite subjects are Vietnamese and Maths.
nhớ tít
study well
1. I study at International Secondary school.
2. I am in grade six and I am in class 6A .
3,There are three buildings and a swimming pool in my school.
4. my class is on the first floor of the building A.
5.My favourite subject are Vietnames and Maths.
a) x2 - 4y2
= x2 - ( 2y )2
= ( x - 2y )( x + 2y )
b) x2 + x - 12
= x2 - 3x + 4x - 12
= x( x - 3 ) + 4( x - 3 )
= ( x - 3 )( x + 4 )
c) x2 + 2xy + y2 - 11
= ( x2 + 2xy + y2 ) - 11
= ( x + y )2 - ( √11 )2
= ( x + y - √11 )( x + y + √11 )
d) x4 + 1
= ( x4 + 2x2 + 1 ) - 2x2
= ( x2 + 1 )2 - ( √2x )2
= ( x2 - √2x + 1 )( x2 + √2x + 1 )
a) \(x^2-4y^2\)
\(=x^2-\left(2y\right)^2\)
\(=\left(x-2y\right).\left(x+2y\right)\)
b) \(x^2+x-12\)
\(=x^2+4x-3x-12\)
\(=\left(x^2+4x\right)-\left(3x+12\right)\)
\(=x.\left(x+4\right)-3.\left(x+4\right)\)
\(=\left(x+4\right).\left(x-3\right)\)
c) \(x^2+2xy+y^2-11\)
\(=\left(x^2+2xy+y^2\right)-11\)
\(=\left(x+y\right)^2-11\)
\(=\left(x+y\right)^2-\left(\sqrt{11}\right)^2\)
\(=\left(x+y-\sqrt{11}\right).\left(x+y+\sqrt{11}\right)\)